The Structural Consequences of Downsizing - DeWitt, Rocki-Lee (Organization Science, 1993)
This paper examines the impact of downsizing strategy on dimensions and types of organizational structure. Four downsizing strategies are developed to address organization and environment decline. Understanding where and how these strategies modify an organization's activities helps clarity how downsizing impacts organization structure. Propositions are offered that show how downsizing can result in both mechanistic and organic shifts in organization structure. Mechanistic shifts are caused by downsizing strategies that increase the domain of an organization and the structural processes used to support that domain. Organic shifts are caused by downsizing strategies that decrease the domain of an organization and the structural processes used to support that domain. The rationale provided for these shifts offers a strategic explanation for decreases in administrative intensity that lag decreases in organization size. Propositions about the impact of downsizing on organizational structure are offered as a stimulus to further thought and research.